2016
DOI: 10.9734/bjmmr/2016/20457
|View full text |Cite
|
Sign up to set email alerts
|

Relating Mandibular Incisor to the Lingual Frenum in Dentulous and Edentulous (Complete Denture Wearers) Subjects: An in vitro Study

Abstract: Aim and Objectives: This study is determined the vertical distance between lingual frenum and incisal edge of mandibular central incisors in dentulous subject and edentulous denture wearer subjects and their variation in different age groups and sex. Materials and Methods: This study involved 120 dentulous subjects (60 men, 60 women) and 20 complete denture wearers. Depending upon the age, the dentulous subjects were divided into three groups. Each group consisted of 40 subjects (20 men, 20 women). Group I con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…indicated that the distance between lingual frenum and incisal edges of mandibular incisors can be used as a reliable landmark when lingual frenum is recorded during function. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…indicated that the distance between lingual frenum and incisal edges of mandibular incisors can be used as a reliable landmark when lingual frenum is recorded during function. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…Esthetic is very important and it is a primary concern for everyone regardless of their age. [ 1 ] Edentulous states not only compromise esthetics but also compromise the integrity of the masticatory process. [ 2 ]An edentulous state also causes loss of the occlusal plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation